Tribal Archives, Traditional Knowledge, and Local Contexts: Why the “s” Matters - Kimberly Christen (Journal of Western Archives, 2015)
In this article I examine the landscape of tribal or Indigenous archival management as it relates to digital assets and, more specifically, how these might help us reimagine the intellectual property needs of local, traditional, and indigenous communities, libraries, archives, and museums as they seek to manage, preserve, and reuse their digital cultural heritage. The colonial collecting project was a destructive mechanism by which Native materials were unhinged from their local places and knowledge and at the same time used as markers of Native erasure. As part of a practical solution to contemporary intellectual property dilemmas faced by Indigenous peoples globally due in large part to the residue of the colonial landscape, I will introduce the Local Contexts project and the Traditional Knowledge License and Label platform (www.localcontexts.org) as one intervention into the sometimes-confusing arena of Indigenous intellectual property rights and the digital commons.